Retracted Article: Controllable color emission of platinum(ii) complexes and their application in light-emitting diodes (LEDs). Issue 27 (24th June 2021) - Li, Bao-Ning; Wang, Jia-Jun; Fu, Peng-Yan; Wang, Shi-Cheng; Pan, Mei
Abstract : A series of platinum(ii ) complexes are applicable in barcode and color changeable logo design, and made into facile LED with maximum output of 8434 cd m −2 and external quantum efficiency (EQE) of 2.58%. Abstract : A series of platinum(ii ) complexes with controllable color emission obtained by regulating intra/intermolecular interactions have been synthesized. These complexes are highly emissive both in solution and in the solid state with microsecond lifetimes, attributed to the single molecular ( 3 IL), excimer, and aggregation emission from their different excited states. All complexes display interesting color changeable photoluminescence depending on concentrations, excitation wavelengths, and good/poor solvents, and exhibit reversible vapochromic/mechanochromic behaviors, which are applicable in emission readable barcode modules and color changeable logo design. Furthermore, using the complexes as emitting materials coated on commercial NUV-LED chips, bright yellow to orange luminescence with a maximum output of 8434 cd m −2 and external quantum efficiency (EQE) of 2.58% could be achieved, providing a facile method to apply platinum(ii ) complexes in the solid state lighting field.